2012
DOI: 10.1111/j.1365-2133.2011.10764.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of carbon ion radiotherapy for skin carcinomas in 45 patients

Abstract: The results demonstrated that heavy ion RT offers high local tumour control and progression-free survival rates without significant radiation-induced toxicity for patients with skin carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
(61 reference statements)
0
20
0
Order By: Relevance
“…Our own studies have shown that carbon ion radiotherapy offers a high degree of control for targeting tumors and increases progression-free survival rates without significant radiation-induced toxicity in skin carcinoma patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Our own studies have shown that carbon ion radiotherapy offers a high degree of control for targeting tumors and increases progression-free survival rates without significant radiation-induced toxicity in skin carcinoma patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…With this approach, the RBE weighted rather than the absorbed dose is optimized, prescribed, recorded, and reported. More recently, also IMP has implemented a model to modulate the absorbed dose according to the variation of the RBE …”
Section: Introductionmentioning
confidence: 99%
“…More recently, also IMP has implemented a model to modulate the absorbed dose according to the variation of the RBE. 25 It is evident that the same RBE weighted dose may result in two rather different treatments, if different RBE models are used. To understand the limits of retrospective comparison of CIRT results at different institution, to reproduce established clinical results in new facilities, and finally to rationally plan multicentric cooperative clinical trials, it is therefore mandatory to understand the general principles behind the different RBE models and the way they are applied clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy has remained the mainstay of treatment for glioblastoma, but these tumors are often associated with radioresistance (1). Heavy ions represent the best tool for various tumors, especially for radioresistant tumors mediated by hypoxia, due to several advantages over conventional radiotherapy (gamma and X-rays) such as an inverted depthdose distribution, a higher relative biological effectiveness, a reduction in oxygen enhancement ratio, less variation in cell cycle related sensitivity and cells having decreased ability to repair (2).…”
Section: Introductionmentioning
confidence: 99%